2016
DOI: 10.5539/gjhs.v9n2p195
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles in Students of Medical Sciences

Abstract: <p><strong>INTRODUCTION: </strong>learning is a human’s natural tendencies; therefore, the identification of factors affecting it, is very important in fixing problems and deficiencies in educational systems. One of the factors contributing to students’ academic achievement and increased learning outcome is to identify their learning styles leading to better and more satisfying learning. The aim of the present study was to examine learning styles in students of Medical Sciences.</p><… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Another study by Ojeh et al, among preclinical medical students in Barbados (2014) using the validated VARK questionnaire, showed that most preclinical medicals students are multimodal learners [10]. Furthermore, similar conclusions on learning styles have been reported by other studies [11][12][13][14][15].…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Another study by Ojeh et al, among preclinical medical students in Barbados (2014) using the validated VARK questionnaire, showed that most preclinical medicals students are multimodal learners [10]. Furthermore, similar conclusions on learning styles have been reported by other studies [11][12][13][14][15].…”
Section: Introductionsupporting
confidence: 53%
“…With regards to UMST, the results were also not in line with that of Joshi et al In their study, which was done in a private university, it was found that the preferred learning style was multimodal [15], which contradicts the results obtained in this study, in which the dominant style was unimodal (Read/Write). However, Shahrakipour et al's study [11] showed the same results. Interestingly, learning styles show variations among different schools, and educators need to assess their students' learning styles in teaching and learning and in discussing examination results.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation